Magnetic, optical gold nanorods for recyclable photothermal ablation of bacteria - Ramasamy, Mohankandhasamy; Lee, Su Seong; Yi, Dong Kee; Kim, Kwangmeyung (ROYAL SOC CHEMISTRY, 2014)
A new antibacterial gold nanorod (GNR) conjugated magnetic nanoparticle (MNP) composite (GNR MNP) was synthesized successfully for the eradication of antibiotic resistant nosocomial pathogens in water to improve the water quality. The composite was fabricated via the reaction of nucleophilic amine and epoxide carbon moieties with silanes. Tagging of MNP over GNR was confirmed using electron microscopy. Zeta potential measurements were used to study the fundamental surface chemical states of GNR and MNP (before and after surface modification). The synthesized GNR-MNP composite was directly mixed with a bacterial culture suspension and the photo-thermally induced bactericidal effects were evaluated before and after laser treatment. Optical, spectral and electron microscopy results revealed that laser irradiated GNR MNP show a more pronounced bactericidal effect than other disinfecting agents. Further, the results indicate that there is a positive correlation between the bacterial cell mortality and nanoparticle concentration and laser energy used. Interestingly, GNR-MNPs are capable of generating a rapid and reiterated photothermal effect for more than three consecutive cycles with enhanced magnetic separation for repeatable bactericidal application. These results suggest that the fabricated GNR-MNPs are a highly efficient photothermal agent against a wide variety of bacteria, suitable for cleaning real samples like water. Importantly, our method showed superior cell lysing results for both Escherichia coli (E. coli) and Enterococcus faecalis (E. faecalis) compared to conventional heat treatment.
Keywords: METAL NANOPARTICLES; THERMAL-STABILITY; ESCHERICHIA-COLI; FUNCTIONALIZATION; TEMPERATURE; THERAPY; MATRIX; AGENTS; SHAPE